SIDOARJO VOLCANIC MUD AS PROMISING FENTON CATALYST FOR REMOVAL OF CONGO RED DYE - Samuel Parningotan; Lucky Caesar Direstiyani; Sandyanto Adityosulindro (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2024)
Sidoarjo mud is a volcanic mud (VM) that continues erupting in Sidoarjo to this day. The VM has the potential to be used in water treatment technology as a reagent or catalyst due to enormous amount of discharged flow and rich mineral content. Heterogeneous Fenton is one promising process for maximizing the VM potential, however customization is essential to optimize the process. Aim: This study aimed to investigate the catalytic abilities of Sidoarjo VM in Fenton oxidation by several modification approaches, such as calcination (CVM), impregnation-calcination (ICVM), and unmodified (UVM). Methodology and results: Fenton oxidation was carried out in a batch reactor system with the following conditions: initial congo red (CR) concentration= 50 mg/L; VCR=300mL pH=2; agitation speed=300 rpm; catalyst dosage=0.5 g/L; dan H2O2 concentration=485 mg/L. The highest performance results were achieved when the process was combined with adsorption, at 90% (CVM), 55% (ICVM), and 52% (UVM), respectively. Conclusion, significance, and impact study: The Sidoarjo volcanic mud shows high potential as a Fenton catalyst in the UVM modification technique with CVM reveals to be more suitable as an adsorbent.